Modeling the dynamics of failure of the electric shield at the renal glomerulus - Nieto Chaupis, Huber (2017)
The human kidney can be seriously threated in the cases where the presence of bunches of electric charges may cancel its electric shield that plays the protectionist role against the pass of giant proteins through the urine. In this paper we use simple physics equations in order to extract the electric field which exerts force on the negative charge distribution located along the glomerular membrane basement and podocytes. The electric forces might be perceived as input signals inside the framework of the Internet of the Bio-Nano Things. In this paper, we have paid attention to the renal glomerulus which is supposed to be very sensitive to the presence of electric fields because the dipole moment of sugar which is one of the charged electrically components of the blood plasm. We provided a simple example which might explain the continuous degradation of kidney in patients with diagnosis of type-2 diabetes.